Original article Laminar distribution of β-amyloid (Aβ) peptide deposits in the frontal lobe in familial and sporadic Alzheimer’s disease - A. Armstrong, Richard (Folia Neuropathologica, 2015)
To determine whether genetic factors influence frontal lobe degeneration in Alzheimer’s disease (AD), the laminar distributions of diffuse, primitive, and classic β-amyloid (Aβ) peptide deposits were compared in early-onset familial AD (EO-FAD) linked to mutations of the amyloid precursor protein (APP) or presenilin 1 (PSEN1) gene, late-onset familial AD (LO-FAD), and sporadic AD (SAD). The influence of apolipoprotein E (Apo E) genotype on laminar distribution was also studied. In the majority of FAD and SAD cases, maximum density of the diffuse and primitive Aβdeposits occurred in the upper cortical layers, whereas the distribution of the classic Aβ deposits was more variable, either occurring in the lower layers, or a double-peaked (bimodal) distribution was present, density peaks occurring in upper and lower layers. The cortical layer at which maximum density of Aβ deposits occurred and maximum density were similar in EO-FAD, LO-FAD and SAD. In addition, there were no significant differences in distributions in cases expressing Apo E ε4 alleles compared with cases expressing the ε2 or ε3 alleles. These results suggest that gene expression had relatively little effect on the laminar distribution of Aβ deposits in the frontal lobe of the AD cases studied. Hence, the pattern of frontal lobe degeneration in AD is similar regardless of whether it is associated with APP and PSEN1, mutation, allelic variation in Apo E, or with SAD.